Behavior of Malaysian investors towards stock market and investment activities - Ung, Wei Wei (Universiti Malaysia Sarawak (UNIMAS), 2012)
This study aims to examine the Malaysian investors' behavior towards stock market and their trading behavior. In particular, we examine the factors that may influence the behavior ofinvestors and how they behave in their investment decision making. The whole analysis is carned out through a system of simultaneous equation -Two Stages Least Square (2SLS) method. The results show that Malaysian investors are mostly driven by herding behavior. Their trading behavior also influenced by the risks. Besides that, emotional and speculative behavior among Malaysian investors also can be explained in this study.